(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2022)
This study has been carried out in the animal field of the college of agricultural engineering sciences, university of Baghdad, for the period from 12/15/2021 to 1/26 /2022 for 42 d, to investigate the effect of adding different levels of ellagic acid to the diet of broilers, on some physiological characteristics & oxidation indicators in meat compared to vitamin C in meat, 225 Ross 308 chicks were used, divided randomly to five treatments such us: T1: control group without additives to diet, & the other T2, T3, T4 was added ellagic acid (0.25, 0.5 and 0.75 mg/ kg diet) respectively and T5: was added vitamin C 0.5 mg/ kg, the birds were given ellagic acid & vitamin C from day one to the end of the experiment, the study results were showed a significant differences increase (P<0.05) improved at T4 treatment in the first & second week & in T2 and T4. in the 4th and 5th weeks treatment T2 was superior, to show a significant advantage of the control treatment & T1,T2 in the 2nd week for the trait of overweight, in the 4th and 5th weeks the treatment T2 was superior for the total weight gain, there was an improvement in the feed conversion in 4th week in T2, in the 5th week the treatment T2 was superior, there was a significantly superior in T2 for total weight gain rate, there was a significant increase in the feed conversion in T1 and T4 in the 2nd week.